2011
DOI: 10.1039/c0py00321b
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional and biodegradable polyphosphazenes for use as macromolecular anti-cancer drug carriers

Abstract: Using a living cationic polymerisation procedure we synthesised a series of multi-armed poly(organo)phosphazenes with controlled molecular weights and excellent aqueous solubility. The synthetic flexibility of polyphosphazenes was exploited in order to incorporate an acid-sensitive hydrazide linker to the polymer backbone, as well as tumour-targeting folic acid groups. We were then able to attach hydrophobic anti-cancer drug molecules via the pH labile linker and studied its pH-triggered release kinetics from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 64 publications
(74 reference statements)
2
68
0
Order By: Relevance
“…This was carried out firstly as it is expected to alter the hydrophobicity and rigidity of the polyphosphazenes backbone, and hence the properties of the polymers, but more importantly as it increases the spacing between the otherwise densely packed side chains (two chains per repeat unit for polymers 1‐4 ). Furthermore, the addition of amino acid ester units is known to enhance the rate of biodegradation of the polymers . It was observed from turbidity measurements (figure ), that despite the relatively low molar ratio of Jeffamine to ethyl valinate (25/75), the thermoresponsive properties of the resulting poly(organophosphazene) was predominately influenced by the Jeffamine used, suggesting that the ratio of ethylene oxide to propylene oxide has a significant impact on the thermosensitive properties of the resultant poly(organophosphazenes) and thus is an effective option to tailor these properties.…”
Section: Resultsmentioning
confidence: 99%
“…This was carried out firstly as it is expected to alter the hydrophobicity and rigidity of the polyphosphazenes backbone, and hence the properties of the polymers, but more importantly as it increases the spacing between the otherwise densely packed side chains (two chains per repeat unit for polymers 1‐4 ). Furthermore, the addition of amino acid ester units is known to enhance the rate of biodegradation of the polymers . It was observed from turbidity measurements (figure ), that despite the relatively low molar ratio of Jeffamine to ethyl valinate (25/75), the thermoresponsive properties of the resulting poly(organophosphazene) was predominately influenced by the Jeffamine used, suggesting that the ratio of ethylene oxide to propylene oxide has a significant impact on the thermosensitive properties of the resultant poly(organophosphazenes) and thus is an effective option to tailor these properties.…”
Section: Resultsmentioning
confidence: 99%
“…The yield can certainly be improved by optimizing the technique. The method for this cationic polymerization was optimized by laboratory members [110]. The GPC-measurement performed confirmed that a high molecular weight polymer was produced as shown in Figure 4.10.…”
Section: Polymermentioning
confidence: 85%
“…Investigations into amino acid substituted polyphosphazenes have shown degradation time‐frames ranging from a short half‐life of a few months for glycinate to years for valinate derivatives, due to the increased steric shielding of the phosphorus from hydrolytic attack . Furthermore, introducing hydrolysis sensitizing amino acid esters as co‐substituents represents a simple route to fine tune degradation rates . Amino acid units have also been shown to sensitize polyphosphazenes towards hydrolysis when used as spacers between the phosphorus and the organic substituents, that is replacing the ethyl ester with for example allyl groups for photochemical cross‐linking or water solubilizing groups (Figure ) .…”
Section: Degradable Inorganic Polymersmentioning
confidence: 99%
“…Furthermore, post‐polymerization functionalization of the bifunctional polyphosphazene repeat unit offers a unique and facile route to multifunctional macromolecules. This has been utilized to attach mixed substituents to the polyphosphazene backbone, such as tumor‐specific targeting ligands in combination with cleavable drugs . Internal functional groups along the phosphazene backbone offer sites for drug conjugation without affecting the surface properties of the carriers, while peripheral functional groups can operate as targeting or solubilizing moieties.…”
Section: Applications In Nanomedicinementioning
confidence: 99%
See 1 more Smart Citation